الظروف الزمانية والمكانية وأثرها في العقوبة -دراسة مقارنة بين الشريعة والقانون - صالحي, لزهر (My University, 2014)
تمقي ىذه الرسالة الضوء عمى أثر الظروف الزمانية والمكانية عمى العقوبة، والتي تتعمق بأمور تمس كيان الأمة وتدخل في مقوماتيا، ولأنيا وقاية للأف ا رد وصيانة لممجتمع، وفييا حفظ لك ا رمة الإنسان، فالشريعة قد ربطت جميع أحكاميا الفقيية والعقائدية بالزمان والمكان، فإنيا ربطت كذلك أبواب الحدود والجنايات بالزمان والمكان، وىي من خلال تشريعيا لمحدود والقصاص لا تيدف إلى معاقبة الجاني، وانما ت ا رعي الظروف التي ارتكبت فييا الجريمة لأنيا تؤثر عمى العقوبة المقررة، وعند تطبيقيا لمعقوبة ت ا رعي ظروف الجاني، ومكان وزمان التطبيق ، إما إسقاطا أو تأخي ا ر أو تشديدا أو تخفيفا. لأن بعض الأزمنة والأمكنة ليا خصوصية معينة تؤثر عمى كل ما يحوييا. وكذلك المشرّع القانوني قد اعتد بالظروف ومن بينيا الظروف الزمانية والمكانية في مواده القانونية، فربط بعض المعاملات بالزمان والمكان، ويتجمى الأمر أكثر في قانون العقوبات، فقد ربط تشديد العقوبة وتخفيفيا والإعفاء منيا بالظرف الزماني والمكاني الذي تُرتكب فيو الجريمة . والفرق بين الشريعة والقانون في تأثير تمك الظروف عمى العقوبة، أن الشريعة أغمب عقوباتيا بدنية، والتي يتجمى فييا ذلك الأثر أكثر، أما القانون فإنو لم يأخذ في الغالب بتمك العقوبات البدنية، لذلك فإنو يربط تأثير الظروف بالجريمة المرتكبة. Receiving this message light on the impact of the conditions on the temporal and spatial punishment، Which relate to matters affecting the nation and the intervention of an entity in its components, because it is protection for individuals and maintenance of the community, And the keeping of human dignity, Sharia has been linked to all provisions of doctrinal and ideological time and place, they linked the border as well as the doors and felonies time and place, It is through legislation and the limits of retribution is not intended to punish the offender, but also take into account the circumstances in which the offense was committed because they affect the prescribed penalty, and when applied to take into account the circumstances of the death of the offender, and the place and time of the application, Either projection or delays, or tightening or loosening. Because some times and places have a certain impact on the privacy of all it contains. As well as the legislature has got used legal conditions, including temporal and spatial conditions in the legal materials, linkage of certain transactions by time and place, Nowhere is it more in the Penal Code, the penalty is increased linking, mitigate and exemption from the spatial and temporal circumstance that the crime was committed. The difference between the law and the law on the impact of these conditions on the death penalty, Most of the law that sanctions are overweight, and that reflect the impact that more, The law did not take it that corporal punishment, so it connects the impact of circumstances to the crime committed.
شريعة وقانون
Keywords: الزمانية والمكانية/العقوبة/لظروف; temporal and spatial/punishment/conditions